# 2D formulation for Magnetostatic Problems

(Difference between revisions)
 Revision as of 10:03, 2 February 2010 (view source)JMora (Talk | contribs)← Older edit Revision as of 10:09, 2 February 2010 (view source)JMora (Talk | contribs) Newer edit → Line 230: Line 230: ::$::[itex] − \int_{\Omega^{(e)}} \mathbf{B^T} \mathbf{\varepsilon} \mathbf{B} \partial \Omega^{(e)}= + \int_{\Omega^{(e)}} \mathbf{B^T} \mathbf{D} \mathbf{B} \partial \Omega^{(e)}= − \int \int_{A^{(e)}} \mathbf{B^T} \mathbf{\varepsilon} \mathbf{B} d x d y = + \int \int_{A^{(e)}} \mathbf{B^T} \mathbf{D} \mathbf{B} d x d y = − \int_0^1 \int_0^{1-\beta} |\mathbf{J^{(e)}}| \mathbf{B^T} \mathbf{\varepsilon} \mathbf{B} d \alpha d \beta = + \int_0^1 \int_0^{1-\beta} |\mathbf{J^{(e)}}| \mathbf{B^T} \mathbf{D} \mathbf{B} d \alpha d \beta =$ [/itex] ::$::[itex] − = \qquad \qquad |\mathbf{J^{(e)}}| \sum_{p=1}^{n_p} \mathbf{B^T} \mathbf{\varepsilon} \mathbf{B} W_p = + = \qquad \qquad |\mathbf{J^{(e)}}| \sum_{p=1}^{n_p} \mathbf{B^T} \mathbf{D} \mathbf{B} W_p = − |\mathbf{J^{(e)}}| \mathbf{B^T} \mathbf{\varepsilon} \mathbf{B} \sum_{p=1}^{n_p} W_p = + |\mathbf{J^{(e)}}| \mathbf{B^T} \mathbf{D} \mathbf{B} \sum_{p=1}^{n_p} W_p = − \frac{|\mathbf{J^{(e)}}|}{2} \mathbf{B^T} \mathbf{\varepsilon} \mathbf{B} + \frac{|\mathbf{J^{(e)}}|}{2} \mathbf{B^T} \mathbf{D} \mathbf{B}$ [/itex] − ::::$\mathbf{B^T} \mathbf{\varepsilon} \mathbf{B} = + ::::[itex]\mathbf{B^T} \mathbf{D} \mathbf{B} = \begin{bmatrix} \begin{bmatrix} \displaystyle \frac{\partial N_1}{\partial x} & \displaystyle \frac{\partial N_1}{\partial x} & Line 254: Line 254: \end{bmatrix} \end{bmatrix} \begin{bmatrix} \begin{bmatrix} − \displaystyle \varepsilon_x & 0 \\ + \displaystyle \frac{1}{\mu_y} & 0 \\ \, \\ \, \\ − 0 & \displaystyle \varepsilon_y + 0 & \displaystyle \frac{1}{\mu_x} \end{bmatrix} \end{bmatrix} \begin{bmatrix} \begin{bmatrix} Line 270: Line 270: − ::::[itex]\mathbf{B(x,y)^T} \mathbf{\varepsilon} \mathbf{B(x,y)} = + ::::[itex]\mathbf{B(x,y)^T} \mathbf{D} \mathbf{B(x,y)} = − \mathbf{B(\alpha,\beta)^T} \mathbf{[[J^{(e)}]^{-1}]^T} \mathbf{\varepsilon} \mathbf{[J^{(e)}]^{-1}} \mathbf{B(\alpha,\beta)}$ + \mathbf{B(\alpha,\beta)^T} \mathbf{[[J^{(e)}]^{-1}]^T} \mathbf{D} \mathbf{[J^{(e)}]^{-1}} \mathbf{B(\alpha,\beta)}[/itex] − ::::$\mathbf{B^T} \mathbf{\varepsilon} \mathbf{B} = + ::::[itex]\mathbf{B^T} \mathbf{D} \mathbf{B} = \frac{1}{|\mathbf{J^{(e)}}|^2} \frac{1}{|\mathbf{J^{(e)}}|^2} \begin{bmatrix} \begin{bmatrix} Line 291: Line 291: \end{bmatrix} \end{bmatrix} \begin{bmatrix} \begin{bmatrix} − \displaystyle \varepsilon_x & 0 \\ + \displaystyle \frac{1}{\mu_y} & 0 \\ \, \\ \, \\ − 0 & \displaystyle \varepsilon_y + 0 & \displaystyle \frac{1}{\mu_x} \end{bmatrix} \end{bmatrix} \begin{bmatrix} \begin{bmatrix} Line 311: Line 311: − ::::[itex]\mathbf{B^T} \mathbf{\varepsilon} \mathbf{B} = + ::::[itex]\mathbf{B^T} \mathbf{D} \mathbf{B} = \frac{1}{(2 A^{(e)})^2} \frac{1}{(2 A^{(e)})^2} \begin{bmatrix} \begin{bmatrix} Line 323: Line 323: \end{bmatrix} \end{bmatrix} \begin{bmatrix} \begin{bmatrix} − \displaystyle \varepsilon_x & 0 \\ + \displaystyle \frac{1}{\mu_y} & 0 \\ \, \\ \, \\ − 0 & \displaystyle \varepsilon_y + 0 & \displaystyle \frac{1}{\mu_x} \end{bmatrix} \end{bmatrix} \begin{bmatrix} \begin{bmatrix} Line 339: Line 339: − ::::[itex]\mathbf{B^T} \mathbf{\varepsilon} \mathbf{B} = + ::::[itex]\mathbf{B^T} \mathbf{D} \mathbf{B} = \frac{1}{(2 A^{(e)})^2} \frac{1}{(2 A^{(e)})^2} \begin{bmatrix} \begin{bmatrix} Line 347: Line 347: \end{bmatrix} \end{bmatrix} \begin{bmatrix} \begin{bmatrix} − \displaystyle \varepsilon_x & 0 \\ + \displaystyle \frac{1}{\mu_y} & 0 \\ \, \\ \, \\ − 0 & \displaystyle \varepsilon_y + 0 & \displaystyle \frac{1}{\mu_x} \end{bmatrix} \end{bmatrix} \begin{bmatrix} \begin{bmatrix} Line 359: Line 359: ::::[itex] ::::[itex] − \int_{\Omega^{(e)}} \mathbf{B^T} \mathbf{\varepsilon} \mathbf{B} \partial \Omega^{(e)}= + \int_{\Omega^{(e)}} \mathbf{B^T} \mathbf{D} \mathbf{B} \partial \Omega^{(e)}= − A^{(e)} \mathbf{B^T} \mathbf{\varepsilon} \mathbf{B} = + A^{(e)} \mathbf{B^T} \mathbf{D} \mathbf{B} = \frac{1}{4 A^{(e)}} \frac{1}{4 A^{(e)}} \begin{bmatrix} \begin{bmatrix} Line 368: Line 368: \end{bmatrix} \end{bmatrix} \begin{bmatrix} \begin{bmatrix} − \displaystyle \varepsilon_x & 0 \\ + \displaystyle \frac{1}{\mu_y} & 0 \\ \, \\ \, \\ − 0 & \displaystyle \varepsilon_y + 0 & \displaystyle \frac{1}{\mu_x} \end{bmatrix} \end{bmatrix} \begin{bmatrix} \begin{bmatrix} Line 384: Line 384: ::[itex] ::[itex] − \int_{\Omega^{(e)}} \mathbf{N^T} \rho_S \partial \Omega^{(e)} = + \int_{\Omega^{(e)}} \mathbf{N^T} J_S \partial \Omega^{(e)} = − \int \int_{A^{(e)}} \mathbf{N^T} \rho_S d x d y = + \int \int_{A^{(e)}} \mathbf{N^T} J_S d x d y = − \int_0^1 \int_0^{1-\beta} |\mathbf{J^{(e)}}| \mathbf{N^T} \rho_S d \alpha d \beta = + \int_0^1 \int_0^{1-\beta} |\mathbf{J^{(e)}}| \mathbf{N^T} J_S d \alpha d \beta = − |\mathbf{J^{(e)}}| \sum_{p=1}^{n_p} \mathbf{N^T} \rho_S W_p = + |\mathbf{J^{(e)}}| \sum_{p=1}^{n_p} \mathbf{N^T} J_S W_p =$ [/itex] Line 397: Line 397: ::::$::::[itex] − \int_{\Omega^{(e)}} \mathbf{N^T} \rho_S \partial \Omega^{(e)} + \int_{\Omega^{(e)}} \mathbf{N^T} J_S \partial \Omega^{(e)} − = 2 A^{(e)} \left [ \frac{1}{6} \quad \frac{1}{6} \quad \frac{1}{6}\right ]^T \rho_S + = 2 A^{(e)} \left [ \frac{1}{6} \quad \frac{1}{6} \quad \frac{1}{6}\right ]^T J_S − = A^{(e)} \frac{\rho_S}{3} \left [ 1 \quad 1 \quad 1 \right ]^T + = A^{(e)} \frac{J_S}{3} \left [ 1 \quad 1 \quad 1 \right ]^T$ [/itex] Line 413: Line 413: ::::$::::[itex] − \int_{\Omega^{(e)}} \mathbf{N^T} \rho_S \partial \Omega^{(e)} + \int_{\Omega^{(e)}} \mathbf{N^T} J_S \partial \Omega^{(e)} = 2 A^{(e)} \left ( \left [ \frac{1}{2} \quad \frac{1}{2} \quad 0 \right ]^T = 2 A^{(e)} \left ( \left [ \frac{1}{2} \quad \frac{1}{2} \quad 0 \right ]^T + \left [ 0 \quad \frac{1}{2} \quad \frac{1}{2} \right ]^T + \left [ 0 \quad \frac{1}{2} \quad \frac{1}{2} \right ]^T + \left [ \frac{1}{2} \quad 0 \quad \frac{1}{2} \right ]^T \right ) + \left [ \frac{1}{2} \quad 0 \quad \frac{1}{2} \right ]^T \right ) − \frac{1}{6} \rho_S + \frac{1}{6} J_S − = A^{(e)} \frac{\rho_S}{3} \left [ 1 \quad 1 \quad 1 \right ]^T + = A^{(e)} \frac{J_S}{3} \left [ 1 \quad 1 \quad 1 \right ]^T$ [/itex] Line 426: Line 426: − ::$\oint_{\Gamma_q^{(e)}} \mathbf{N^T} \bar D_n \partial \Gamma_q^{(e)}$ + ::$\oint_{\Gamma_q^{(e)}} \mathbf{N^T} \bar q_n \partial \Gamma_q^{(e)}$ − ::$\oint_{\Gamma_V^{(e)}} \mathbf{n^T} \mathbf{N^T} \mathbf{q_n} \partial \Gamma_V^{(e)}$ + ::$\oint_{\Gamma_V^{(e)}} \mathbf{n^T} \mathbf{N^T} \mathbf{q_n} \partial \Gamma_{{A_x}^{(e)}}$

## Revision as of 10:09, 2 February 2010

The 2D Magnetostatic Poisson's equation given by the governing PDE and its boundary conditions:

$A(A_z) = \left[ \frac{\partial}{\partial x}\cdot \left( \frac{1}{\mu_y} \frac{\partial}{\partial x}\right) + \frac{\partial}{\partial y}\cdot \left( \frac{1}{\mu_x} \frac{\partial }{\partial y}\right) \right] A_z(x,y)+ J_z(x,y)=0 ~~ in ~ \Omega$

$B(A_z) = \begin{cases} \left . A_z - \bar A_z = 0 \right |_{\Gamma_{A_z}} & in ~ \Gamma_{\varphi} \\ \, \\ \left . \hat n \vec{H} - \bar H_n = 0 \right |_{\Gamma_{q}} & in ~ \Gamma_{q} \\ \, \\ \left . \displaystyle \frac{\partial A_z}{\partial r} \right |_{\Gamma_{\infty}} \approx \displaystyle - \frac{A_z}{r^{exp}} & in ~ \Gamma_{\infty} \end{cases}$

can be written as (see the General formulation for Magnetostatic Problems):

${ \int_{\Omega} \mathbf{B^T} \mathbf{D} \mathbf{B} \mathbf{a} \partial \Omega + \oint_{\Gamma_{\infty}} \mathbf{N^T} \alpha \mathbf{N} \mathbf{a} \partial \Gamma_{\infty} = \int_{\Omega} \mathbf{N^T} J_S \partial \Omega - \oint_{\Gamma_q} \mathbf{N^T} \bar q_n \partial \Gamma_q - \oint_{\Gamma_V} \mathbf{n^T} \mathbf{N^T} \mathbf{q_n} \partial \Gamma_{\varphi} }$

$\mathbf{K} \mathbf{a} \,= \mathbf{f}$

$\mathbf{K}^{(e)}= \int_{\Omega^{(e)}} \mathbf{B^T} \mathbf{D} \mathbf{B} \partial \Omega^{(e)} + \oint_{\Gamma_{\infty}^{(e)}} \mathbf{N^T} \alpha \mathbf{N} \partial \Gamma_{\infty}^{(e)}$
$\mathbf{f}^{(e)}= \int_{\Omega^{(e)}} \mathbf{N^T} J_S \partial \Omega^{(e)} - \oint_{\Gamma_q^{(e)}} \mathbf{N^T} \bar q_n \partial \Gamma_q^{(e)} - \oint_{\Gamma_{{A_z}^{(e)}}} \mathbf{n^T} \mathbf{N^T} \mathbf{q_n} \partial \Gamma_{\varphi^{(e)}}$

with (n is the number of nodes of the element):

$A_z(x,y) \cong \hat A_z(x,y) = \sum_{i=0}^n N_i (x,y) a_i = \mathbf{N}^{(e)} · \mathbf{a}^{(e)}$

$\mathbf{N^{(e)}} = \begin{bmatrix} N_1 \\ \, \\ N_2 \\ \, \\ \vdots \\ \, \\ N_n \end{bmatrix} \qquad \mathbf{a^{(e)}} = \begin{bmatrix} a_1 \\ \, \\ a_2 \\ \, \\ \vdots \\ \, \\ a_n \end{bmatrix} \qquad \mathbf{B}= \left [ \mathbf{B_1 B_2 ... B_n} \right ] \qquad \mathbf{B_i}= \begin{bmatrix} \displaystyle \frac{\partial N_i}{\partial x} \\ \, \\ \displaystyle \frac{\partial N_i}{\partial y} \end{bmatrix} \qquad \mathbf{D}= \begin{bmatrix} \displaystyle \frac{1}{\mu_y} & 0 \\ \, \\ 0 & \displaystyle \frac{1}{\mu_x} \end{bmatrix}$

$\alpha = \frac{1}{|r-r_0|^{exp}} \qquad with \quad exp=0.5, 1, 2...$

## 2D formulation for Triangular Elements

After applying the numerical integration for triangular elements by using the natural coordinates, we obtain:

$\mathbf{N^{(e)}} = \begin{bmatrix} N_1 & N_2 & N_3 \end{bmatrix} = \begin{bmatrix} L_1 & L_2 & L_3 \end{bmatrix} = \begin{bmatrix} (1-\alpha-\beta) & \alpha & \beta \end{bmatrix} \qquad \mathbf{a^{(e)}} = \begin{bmatrix} a_1 \\ \, \\ a_2 \\ \, \\ a_3 \end{bmatrix}$

$\frac{\partial N_1}{\partial \alpha}=-1 \qquad \frac{\partial N_2}{\partial \alpha}=1 \qquad \frac{\partial N_3}{\partial \alpha}=0 \qquad \frac{\partial N_1}{\partial \beta}=-1 \qquad \frac{\partial N_2}{\partial \beta}=0 \qquad \frac{\partial N_3}{\partial \beta}=1$

$x = N_1 x_1 + N_2 x_2 + N_3 x_3 = ( 1 - \alpha - \beta) x_1 + \alpha x_2 + \beta x_3 \,$

$y = N_1 y_1 + N_2 y_2 + N_3 y_3 = ( 1 - \alpha - \beta) y_1 + \alpha y_2 + \beta y_3 \,$

$\mathbf{J^{(e)}} = \begin{bmatrix} \displaystyle \frac{\partial x}{\partial \alpha} & \displaystyle \frac{\partial y}{\partial \alpha} \\ \quad \\ \displaystyle \frac{\partial x}{\partial \beta} & \displaystyle \frac{\partial y}{\partial \beta} \end{bmatrix} = \begin{bmatrix} - x_1 + x_2 & - y_1 + y_2 \\ - x_1 + x_3 & - y_1 + y_3 \end{bmatrix} \qquad \mathbf{|J^{(e)}|} = 2 A^{(e)}$

$\mathbf{B(\alpha,\beta)}=\mathbf{J^{(e)}} \mathbf{B(x,y)} \qquad \mathbf{B(x,y)}= \mathbf{[J^{(e)}]^{-1}} \mathbf{B(\alpha,\beta)}$

$\mathbf{B}= \begin{bmatrix} \displaystyle \frac{\partial N_1}{\partial x} & \displaystyle \frac{\partial N_2}{\partial x} & \displaystyle \frac{\partial N_3}{\partial x}\\ \, \\ \displaystyle \frac{\partial N_1}{\partial y} & \displaystyle \frac{\partial N_2}{\partial y} & \displaystyle \frac{\partial N_3}{\partial y} \end{bmatrix} = \frac{1}{|\mathbf{J^{(e)}}|} \begin{bmatrix} \displaystyle \frac{\partial y}{\partial \beta} & \displaystyle -\frac{\partial y}{\partial \alpha} \\ \displaystyle -\frac{\partial x}{\partial \beta} & \displaystyle \frac{\partial x}{\partial \alpha} \end{bmatrix} \begin{bmatrix} \displaystyle \frac{\partial N_1}{\partial \alpha} & \displaystyle \frac{\partial N_2}{\partial \alpha} & \displaystyle \frac{\partial N_3}{\partial \alpha}\\ \, \\ \displaystyle \frac{\partial N_1}{\partial \beta} & \displaystyle \frac{\partial N_2}{\partial \beta} & \displaystyle \frac{\partial N_3}{\partial \beta} \end{bmatrix}$

$\mathbf{B} = \frac{1}{2 A^{(e)}} \begin{bmatrix} - y_1 + y_3 & - y_2 + y_1 \\ - x_3 + x_1 & - x_1 + x_2 \end{bmatrix} \begin{bmatrix} -1 & 1 & 0 \\ -1 & 0 & 1 \end{bmatrix} = \frac{1}{2 A^{(e)}} \begin{bmatrix} - y_3 + y_2 & - y_1 + y_3 & - y_2 + y_1 \\ x_3 - x_2 & - x_3 + x_1 & - x_1 + x_2 \end{bmatrix}$

### Stiffness Matrix K(e)

$\int_{\Omega^{(e)}} \mathbf{B^T} \mathbf{D} \mathbf{B} \partial \Omega^{(e)}= \int \int_{A^{(e)}} \mathbf{B^T} \mathbf{D} \mathbf{B} d x d y = \int_0^1 \int_0^{1-\beta} |\mathbf{J^{(e)}}| \mathbf{B^T} \mathbf{D} \mathbf{B} d \alpha d \beta =$
$= \qquad \qquad |\mathbf{J^{(e)}}| \sum_{p=1}^{n_p} \mathbf{B^T} \mathbf{D} \mathbf{B} W_p = |\mathbf{J^{(e)}}| \mathbf{B^T} \mathbf{D} \mathbf{B} \sum_{p=1}^{n_p} W_p = \frac{|\mathbf{J^{(e)}}|}{2} \mathbf{B^T} \mathbf{D} \mathbf{B}$

$\mathbf{B^T} \mathbf{D} \mathbf{B} = \begin{bmatrix} \displaystyle \frac{\partial N_1}{\partial x} & \displaystyle \frac{\partial N_1}{\partial y} \\ \, \\ \displaystyle \frac{\partial N_2}{\partial x} & \displaystyle \frac{\partial N_2}{\partial y} \\ \, \\ \displaystyle \frac{\partial N_3}{\partial x} & \displaystyle \frac{\partial N_3}{\partial y} \end{bmatrix} \begin{bmatrix} \displaystyle \frac{1}{\mu_y} & 0 \\ \, \\ 0 & \displaystyle \frac{1}{\mu_x} \end{bmatrix} \begin{bmatrix} \displaystyle \frac{\partial N_1}{\partial x} & \displaystyle \frac{\partial N_2}{\partial x} & \displaystyle \frac{\partial N_3}{\partial x}\\ \, \\ \displaystyle \frac{\partial N_1}{\partial y} & \displaystyle \frac{\partial N_2}{\partial y} & \displaystyle \frac{\partial N_3}{\partial y} \end{bmatrix}$

$\mathbf{B(x,y)^T} \mathbf{D} \mathbf{B(x,y)} = \mathbf{B(\alpha,\beta)^T} \mathbf{[[J^{(e)}]^{-1}]^T} \mathbf{D} \mathbf{[J^{(e)}]^{-1}} \mathbf{B(\alpha,\beta)}$

$\mathbf{B^T} \mathbf{D} \mathbf{B} = \frac{1}{|\mathbf{J^{(e)}}|^2} \begin{bmatrix} \displaystyle \frac{\partial N_1}{\partial \alpha} & \displaystyle \frac{\partial N_1}{\partial \beta} \\ \, \\ \displaystyle \frac{\partial N_2}{\partial \alpha} & \displaystyle \frac{\partial N_2}{\partial \beta} \\ \, \\ \displaystyle \frac{\partial N_3}{\partial \alpha} & \displaystyle \frac{\partial N_3}{\partial \beta} \end{bmatrix} \begin{bmatrix} \displaystyle \frac{\partial y}{\partial \beta} & \displaystyle -\frac{\partial x}{\partial \beta} \\ \displaystyle -\frac{\partial y}{\partial \alpha} & \displaystyle \frac{\partial x}{\partial \alpha} \end{bmatrix} \begin{bmatrix} \displaystyle \frac{1}{\mu_y} & 0 \\ \, \\ 0 & \displaystyle \frac{1}{\mu_x} \end{bmatrix} \begin{bmatrix} \displaystyle \frac{\partial y}{\partial \beta} & \displaystyle -\frac{\partial y}{\partial \alpha} \\ \displaystyle -\frac{\partial x}{\partial \beta} & \displaystyle \frac{\partial x}{\partial \alpha} \end{bmatrix} \begin{bmatrix} \displaystyle \frac{\partial N_1}{\partial \alpha} & \displaystyle \frac{\partial N_2}{\partial \alpha} & \displaystyle \frac{\partial N_3}{\partial \alpha}\\ \, \\ \displaystyle \frac{\partial N_1}{\partial \beta} & \displaystyle \frac{\partial N_2}{\partial \beta} & \displaystyle \frac{\partial N_3}{\partial \beta} \end{bmatrix}$

$\mathbf{B^T} \mathbf{D} \mathbf{B} = \frac{1}{(2 A^{(e)})^2} \begin{bmatrix} -1 & -1 \\ 1 & 0 \\ 0 & 1 \end{bmatrix} \begin{bmatrix} - y_1 + y_3 & - x_3 + x_1 \\ - y_2 + y_1 & - x_1 + x_2 \end{bmatrix} \begin{bmatrix} \displaystyle \frac{1}{\mu_y} & 0 \\ \, \\ 0 & \displaystyle \frac{1}{\mu_x} \end{bmatrix} \begin{bmatrix} - y_1 + y_3 & - y_2 + y_1 \\ - x_3 + x_1 & - x_1 + x_2 \end{bmatrix} \begin{bmatrix} -1 & 1 & 0 \\ -1 & 0 & 1 \end{bmatrix}$

$\mathbf{B^T} \mathbf{D} \mathbf{B} = \frac{1}{(2 A^{(e)})^2} \begin{bmatrix} - y_3 + y_2 & x_3 + x_2 \\ - y_1 + y_3 & - x_3 + x_1 \\ - y_2 + y_1 & - x_1 + x_2 \end{bmatrix} \begin{bmatrix} \displaystyle \frac{1}{\mu_y} & 0 \\ \, \\ 0 & \displaystyle \frac{1}{\mu_x} \end{bmatrix} \begin{bmatrix} - y_3 + y_2 & - y_1 + y_3 & - y_2 + y_1 \\ x_3 + x_2 & - x_3 + x_1 & - x_1 + x_2 \end{bmatrix}$

$\int_{\Omega^{(e)}} \mathbf{B^T} \mathbf{D} \mathbf{B} \partial \Omega^{(e)}= A^{(e)} \mathbf{B^T} \mathbf{D} \mathbf{B} = \frac{1}{4 A^{(e)}} \begin{bmatrix} - y_3 + y_2 & x_3 + x_2 \\ - y_1 + y_3 & - x_3 + x_1 \\ - y_2 + y_1 & - x_1 + x_2 \end{bmatrix} \begin{bmatrix} \displaystyle \frac{1}{\mu_y} & 0 \\ \, \\ 0 & \displaystyle \frac{1}{\mu_x} \end{bmatrix} \begin{bmatrix} - y_3 + y_2 & - y_1 + y_3 & - y_2 + y_1 \\ x_3 + x_2 & - x_3 + x_1 & - x_1 + x_2 \end{bmatrix}$

$\oint_{\Gamma_{\infty}^{(e)}} \mathbf{N^T} \alpha \mathbf{N} \partial \Gamma_{\infty}^{(e)}$

### Source Vector f(e)

$\int_{\Omega^{(e)}} \mathbf{N^T} J_S \partial \Omega^{(e)} = \int \int_{A^{(e)}} \mathbf{N^T} J_S d x d y = \int_0^1 \int_0^{1-\beta} |\mathbf{J^{(e)}}| \mathbf{N^T} J_S d \alpha d \beta = |\mathbf{J^{(e)}}| \sum_{p=1}^{n_p} \mathbf{N^T} J_S W_p =$

Linear case (np=1 integration point):

$N=\left [ \frac{1}{3} \quad \frac{1}{3} \quad \frac{1}{3}\right ] \qquad W_i=\frac{1}{2}\,$
$\int_{\Omega^{(e)}} \mathbf{N^T} J_S \partial \Omega^{(e)} = 2 A^{(e)} \left [ \frac{1}{6} \quad \frac{1}{6} \quad \frac{1}{6}\right ]^T J_S = A^{(e)} \frac{J_S}{3} \left [ 1 \quad 1 \quad 1 \right ]^T$

$p=1 \qquad N=\left [ \frac{1}{2} \quad \frac{1}{2} \quad 0\right ] \qquad W_1=\frac{1}{6}\,$
$p=2 \qquad N=\left [ 0 \quad \frac{1}{2} \quad \frac{1}{2}\right ] \qquad W_2=\frac{1}{6}\,$
$p=3 \qquad N=\left [ \frac{1}{2} \quad 0 \quad \frac{1}{2}\right ] \qquad W_3=\frac{1}{6}\,$

$\int_{\Omega^{(e)}} \mathbf{N^T} J_S \partial \Omega^{(e)} = 2 A^{(e)} \left ( \left [ \frac{1}{2} \quad \frac{1}{2} \quad 0 \right ]^T + \left [ 0 \quad \frac{1}{2} \quad \frac{1}{2} \right ]^T + \left [ \frac{1}{2} \quad 0 \quad \frac{1}{2} \right ]^T \right ) \frac{1}{6} J_S = A^{(e)} \frac{J_S}{3} \left [ 1 \quad 1 \quad 1 \right ]^T$

$\oint_{\Gamma_q^{(e)}} \mathbf{N^T} \bar q_n \partial \Gamma_q^{(e)}$
$\oint_{\Gamma_V^{(e)}} \mathbf{n^T} \mathbf{N^T} \mathbf{q_n} \partial \Gamma_{{A_x}^{(e)}}$